2016
DOI: 10.1002/15-0783
|View full text |Cite
|
Sign up to set email alerts
|

Prey‐mediated behavioral responses of feeding blue whales in controlled sound exposure experiments

Abstract: Behavioral response studies provide significant insights into the nature, magnitude, and consequences of changes in animal behavior in response to some external stimulus. Controlled exposure experiments (CEEs) to study behavioral response have faced challenges in quantifying the importance of and interaction among individual variability, exposure conditions, and environmental covariates. To investigate these complex parameters relative to blue whale behavior and how it may change as a function of certain sound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 44 publications
1
59
2
Order By: Relevance
“…They then compared numerous dive parameters in intentionally unexposed Blainville's beaked whales to those in sonar CEEs using identical highresolution behavioral metrics. Similarly, studies of diving kinematics and feeding strategies of blue whales Balaenoptera musculus in relation to prey distribution have provided critical insight into the interpretation of responses of feeding whales during CEEs (Friedlaender et al 2016). Furthermore, baseline acoustic data from the tags have contributed to understanding the typical animal distribution in study areas before, during and after exposure to sound (McCarthy et al 2011, Tyack et al 2011, Yack et al 2013.…”
Section: Methodological Approaches To Measuring Marine Mammal Behaviomentioning
confidence: 99%
See 3 more Smart Citations
“…They then compared numerous dive parameters in intentionally unexposed Blainville's beaked whales to those in sonar CEEs using identical highresolution behavioral metrics. Similarly, studies of diving kinematics and feeding strategies of blue whales Balaenoptera musculus in relation to prey distribution have provided critical insight into the interpretation of responses of feeding whales during CEEs (Friedlaender et al 2016). Furthermore, baseline acoustic data from the tags have contributed to understanding the typical animal distribution in study areas before, during and after exposure to sound (McCarthy et al 2011, Tyack et al 2011, Yack et al 2013.…”
Section: Methodological Approaches To Measuring Marine Mammal Behaviomentioning
confidence: 99%
“…Additional methodological ad vances included using active fisheries acoustics to measure prey distribution for feeding baleen whales, resulting in key insights into baseline foraging ecology (e.g. Goldbogen et al 2013) and the context-dependent nature of behavioral responses (Friedlaender et al 2016). While some SOCAL-BRS data were still being collected and analyzed at the time of this review, many results were already published, notably for blue and beaked whales.…”
Section: Socal-brsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, McKenna et al (2015) found that feeding blue whales exhibited a limited and inconsistent response repertoire during close approaches by large vessels near ship channels off the ports of Los Angeles and Long Beach. Likewise, deep-feeding blue whales showed stronger responses to presentation of anthropogenic noise than other behavioral states (Friedlaender et al 2016).…”
Section: Introductionmentioning
confidence: 96%